The Effects of Early Nutritional Intervention on Oral Mucositis and Nutritional Status of Patients With Head and Neck Cancer Treated With Radiotherapy - Zheng, Zhuangzhuang; Zhao, Xin; Zhao, Qin; Zhang, Yuyu; Liu, Shiyu; Liu, Zijing; Meng, Lingbin; Xin, Ying; Jiang, Xin (Frontiers in Oncology, 2021)
Radiation-induced oral mucositis (RIOM) is a common side effect after radiotherapy (RT) in head and neck cancer (HNC) patients. RIOM patients with severe pain have difficulty in eating, which increases the incidence of malnutrition and affects patients' quality of life and the process of RT. The mechanism of RIOM is not fully understood, and inflammatory response and oxidative stress appear to be important for RIOM occurrence and development. The nutritional status of patients is very important for their RT tolerance and recovery. Malnutrition, which can lead to anemia, low protein, decreased immunity and other problems, is an important clinical factor affecting tumor progression and treatment. Recent studies have shown that early nutritional intervention can ameliorate oral mucositis and nutritional status of patients with HNC. However, in clinical practice, early nutritional intervention for patients with HNC is not a conventional intervention strategy. Therefore, this review summarized the possible pathogenesis of RIOM, commonly used assessment tools for malnutrition in patients, and recent studies on the effects of early nutritional interventions on RIOM and nutritional status of patients with HNC. We hope to provide the basis and reference for the clinical application of early nutritional intervention models.